Analisis Konten Komparatif Bahan Ajar IPA Tata Surya: Studi Kritis Kurikulum KTSP-Merdeka - Sintiyani Fatikha Rizki; Adinda Kusuma Mouristi; Firly Hernanda (CV. Akademi Merdeka, 2025)
This study aims to analyze and compare science textbooks focused on the solar system for fourth-grade elementary school students. A literature review identifies several essential criteria that quality textbooks must fulfill. If deficiencies are found, revisions are necessary to ensure effective teaching. Science textbooks should also include activities that promote critical thinking among students. The research evaluates the content feasibility, language use, and presentation suitability of science textbooks aligned with the KTSP and Merdeka Curriculum regarding solar system material. A qualitative descriptive approach is employed, concentrating on science textbooks about the solar system for fourth-grade students. Data collection involves observation, documentation, and analysis of errors and conceptual accuracy within the textbooks. The findings reveal minor errors in the KTSP textbooks, particularly in language and presentation aspects. In contrast, the Merdeka Curriculum textbooks are deemed suitable as learning resources for sixth-grade students. Their comprehensive content, simple and understandable language, and engaging, interactive presentation make these books effective in supporting the learning process. Overall, the Merdeka Curriculum textbooks are more appropriate than the KTSP textbooks as teaching materials for elementary science.